The Effect of Vanadium Doped on the Structural Parameters and Some Optical Properties of (ZnO)Thin Films Prepared by Chemical Spray (Journal of the College of Basic Education, 2022)
In this research; The effect of vanadium doped ZnO at different ratios (1,3,5,7)% on the structural parameters and some optical properties such as, (Transmittance, Absorptance) has been studied. These thin films were prepared by the chemical spray pyrolysis and deposited on the glass substrates heated at (450 oC).The study showed that; The addition of vanadium changes the transmittance and absorptance values, also,The structural parameters values are changed for the prepared thin films.